Antibacterial Activity of Ethanolic Extract of Sangkareho (Callicarpa longifolia Lam.) against Staphylococcus epidermidis - Susi Novaryatiin; Asma'ul Ayuriska Sari; Evi Mulyani (Borneo Journal of Pharmacy, 2018)
One of the plants believed as traditional medicine by the Dayak tribes in Central Kalimantan was Sangkareho (Callicarpa longifolia Lam.). This plant was usually used as traditional medicine by society in Puruk Cahu, Murung Raya Regency, Central Kalimantan and empirically believed could cure skin disease such as wound infection. This study was aimed to determine the antibacterial activity of ethanolic extract of Sangkareho (Callicarpa longifolia Lam). Antibacterial activity of ethanolic extract of Sangkareho was performed using disc diffusion technique, with four variations of concentration of 1%, 5%, 10%, and 15%. In this present study showed that ethanolic extract of Sangkareho has antibacterial activity against Staphylococcus epidermidis, wherein the resulting inhibition zone diameter was 7.3±0.8 mm, 8.3±1.2 mm, 10.5±0.5 mm, and 12.2±0.7 mm, respectively. Further research is needed to obtain an antibacterial activity of the fraction of Sangkareho.